Application of enzyme-digested soy protein hydrolysate on hydroponic-planted lettuce: effects on lettuce phytochemical contents, biochemical profiles and physical properties - Shaila, Mohana Dass (2022)
The global population is growing exponentially over time and it is vital to produce much more food to meet the increase in demand for food. Similarly, more traditional agricultural arable lands are diminishing due to excessive infrastructure development, extreme climate change , and natural disasters Advanced cultivation technologies have been developed and practice . d worldwide to overcome challenges such as climate change as well as to boost sufficie nt security . food production to meet the rising demands as well as to improve food Hydroponic farming has been reported as one of the agricultural methods of growing crops indoors an alternative approach for foo , especially in urban areas and it has become d production to cope with food supply challenges as well as helps to decrease the need for more land farming. The hydroponic system is a modern agriculture method of growing crops using minerals nutrient solutions instead of soil where the plant rootsrich are suspended in nutrient solution . the Generally, parameters such as nutrient solution pH and electrical conductivity (EC) are set to the desired value according to the crop type in the hydroponic system to achieve optimal crop growt hydrolysat h . Protein e is a mixture of various sizes of peptide fragments and free amino iiiii acids produced through hydrolysis of a protein-rich source. Protein hydrolysate can be produced from animal or plant protein that can further be used as biostimulants in agriculture to stimulate crop cultivation. On the other hand, soybean waste is also known as Okara, a by-product of soy milk and soy tofu production. Currently, soybean waste is utilized as food additives, animal feed as well as a source of fertilizer. A considerable amount of this soybean waste is also discarded in landfills which causes environmental problems. At present, the application of soybean waste in hydroponic planting remains unexplored. In this study, soybean waste-derived protein hydrolysate was produced via an enzymatic hydrolysis approach by using protease (alcalase). After the enzymatic hydrolysis process, the prepared protein hydrolysate was tested on hydroponic-planted green coral lettuce. The effects of soy protein hydrolysate (SPH) as a hydroponic nutrient supplement were assessed by determining the physical properties, phytochemical contents, and biochemical profiles of the hydroponic-planted lettuce. Based on the results obtained, the length and fresh weight of the hydroponic-planted lettuce were at a peak when treated with 0.01 mg/mL of SPH whereas, for other physical properties such as lettuce leaf surface area, root length, and root weight, no significant difference was detected. There were increasing concentrations of total phenolic content (TPC), total flavonoid content (TFC), and total hydroxycinnamic acid content (THC) observed in lettuces that were treated with 0 to 0.01 mg/mL of SPH compared to control. Whereas, lettuce treated with 0.01 mg/mL of SPH has the highest Vitamin C content. In addition, the concentrations of chlorophyll a, chlorophyll b, and carotenoid in hydroponic-planted lettuce were the highest when treated with 0.01 iv mg/mL of SPH compared to control. The presence of five mineral elements (iron, copper, zinc, magnesium, and calcium) was detected in all lettuce. However, there was no significant difference detected in mineral contents of SPH-treated hydroponic-planted lettuces, compared to the control group except for a higher magnesium content detected in lettuce samples treated at the highest SPH concentration (0.1 mg/mL). Lastly, higher catalase and superoxide dismutase contents were detected in lettuces treated with SPH concentrations ranging from 0.001 to 0.1 and 0.01-0.1 mg/mL, respectively, compared to the control group.